IMF performance in the run-up to the financial and economic crisis IMF surveillance in 2004-07. - Lamdany, Ruben 1954-; Wagner, Nancy L. (Nancy Louise) (Evaluation report / IEO, 2011)
"This evaluation assesses the performance of IMF surveillance in the run-up to the global financial and economic crisis and offers recommendations on how to strengthen the IMF's ability to discern risks and vulnerabilities and to warn the membership in the future. It finds that the IMF provided few clear warnings about the risks and vulnerabilities associated with the impending crisis before its outbreak. The banner message was one of continued optimism after more than a decade of benign economic conditions and low macroeconomic volatility. The IMF, in its bilateral surveillance of the United States and the United Kingdom, largely endorsed policies and financial practices that were seen as fostering rapid innovation and growth. The belief that financial markets were fundamentally sound and that large financial institutions could weather any likely problem lessened the sense of urgency to address risks or to worry about possible severe adverse outcomes. Surveillance also paid insufficient attention to risks of contagion or spillovers from a crisis in advanced economies. Advanced economies were not included in the Vulnerability Exercise launched after the Asian crisis, despite internal discussions and calls to this effect from Board members and others."--Executive summary.